2019
DOI: 10.1017/s1755773919000055
|View full text |Cite
|
Sign up to set email alerts
|

The costs of interest representation – a resource perspective on informational lobbying

Abstract: While expert information and information on public preferences are seen as key resources that interest groups provide to policymakers, little is known about the resources that are necessary to acquire such information. Existing scholarship argues that financial resources enhance a group’s ability to supply information, which could be problematic as it suggests that resource poor groups are disadvantaged when lobbying policymakers. Applying a resource perspective to informational lobbying, this paper argues tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 51 publications
(89 reference statements)
2
33
0
2
Order By: Relevance
“…Member involvement relates to those organizational features that are aimed at connecting, engaging, and interacting with members, while ensuring that the group reflects members' preferences and information. This organizational dimension speaks to the idea of representation capacity, defined as the ability of groups to speak on behalf of their members (Flöthe, 2019b). Groups that intend to foster their intermediate role are expected to have organizational mechanisms that connect them with their membership base.…”
Section: Member Involvementmentioning
confidence: 99%
“…Member involvement relates to those organizational features that are aimed at connecting, engaging, and interacting with members, while ensuring that the group reflects members' preferences and information. This organizational dimension speaks to the idea of representation capacity, defined as the ability of groups to speak on behalf of their members (Flöthe, 2019b). Groups that intend to foster their intermediate role are expected to have organizational mechanisms that connect them with their membership base.…”
Section: Member Involvementmentioning
confidence: 99%
“…The information-exchange perspective is among the most frequently used theoretical approaches in interest group scholarship. Most studies to date have addressed the supply side of interest groups in information exchanges with decision-makers (see for instance Flöthe, 2019a;Tallberg et al, 2018;Klüver, 2013;Chalmers, 2013;De Bruycker, 2016). Our paper has contributed to this literature by focusing on the decision-makers' side of information exchanges and seeking to explain variation in the information demands of decision-makers across the globe in their exchanges with interest groups and INGOs.…”
Section: Resultsmentioning
confidence: 99%
“…Producing technical information is however a costly and time-consuming endeavor. Indeed, comparative research has shown that mostly wealthy interest organizations are able to supply technical information (Flöthe, 2019a). Hence, we can presume that the supply of technical information by interest groups is less secure in developing countries where societal interests are deprived and lack the financial capabilities to produce and communicate technical expertise.…”
Section: Explaining Technical and Political Demands Across Politiesmentioning
confidence: 99%
See 2 more Smart Citations